Green and rapid synthesis of biomass carbon dot-based fluorescence sensing for the sensitive determination of oxytetracycline. Issue 12 (8th March 2023) - Li, Qianji; Wu, Xiwen; Zhang, Xiaohuan; Su, Wenen; Tan, Yan; Fan, Pengfei; Liu, Jinquan; Yang, Shengyuan
Abstract : Green and rapid synthesis of biomass carbon dots for the sensitive fluorescence sensing determination of oxytetracycline. Abstract : Eco-friendly biomass carbon dots (CDs) with blue fluorescence emission were rapidly synthesized by a microwave method. Based on the inner filter effect (IFE) between oxytetracycline (OTC) and CDs, the fluorescence of CDs could be selectively quenched by OTC. Therefore, a simple and time-saving fluorescence sensing system for the detection of OTC was established. Under optimal experimental conditions, the concentration of OTC showed a good linear relationship with fluorescence quenching values (Δ F ) in the range of 4.0–100.0 μmol L −1, a corresponding correlation coefficient ( r ) of 0.9975, and a detection limit of 0.12 μmol L −1 . The method has the advantages of low cost, time-saving, and green synthesis that could be used for the determination of OTC. Moreover, possessing high sensitivity and specificity, this fluorescence sensing method was successfully applied for detecting OTC in milk, indicating its potential applications in food safety.